Praktek Jual Beli di Toko Anugrah Perspektif Ekonomi Syariah - Ahmad Syaifuddin Romli; Reza Hilmy Luayyin; Ardli, Muhammad Nabat (JSE: Jurnal Sharia Economica, 2024)
Everyone will definitely need other people. More so in terms of human needs. one of them is in the field of trade related to materials. One of them is in the Anugrah Shop. The buying and selling practices carried out at Toko Anugrah have been running for a long time. How to do it is by observation, interviews, and documentation used to collect data. The tool used is the interview guide as the main tool. Data processing begins with data collection, data reduction, data organisation, and data validation. Triangulation techniques were used when testing the validity of the data. The results of the study state that this research aims to explore the practice of buying and selling at Toko Anugrah from the perspective of Islamic economics. Islamic economics emphasises the principles of fairness, transparency, and halalness in every transaction. This study explains how Toko Anugrah applies these principles in its daily operations, particularly in pricing, quality of goods, and the contract process. Through the implementation of the murabaha contract, this shop sells goods with a clear profit margin without the element of usury. The return policy is also set fairly, ensuring customer satisfaction and trust. The results show that the buying and selling practices at Toko Anugrah not only increase customer trust but also provide sustainable profits and blessings for the store. Thus, Toko   Keywords:  Buyying, Salling, Sharia Economics